Relations between Levels of Government in Handling the Covid-19 pandemic in Indonesia: A Study on Relations between the Central Government and the Provincial Government of DKI Jakarta - Achmad Lutfi; Desy Hariyati (Indonesian Association for Public Administration (IAPA), 2020)
The Covid-19 pandemic has plagued various countries in this hemisphere. The spread of this pandemic has a significant impact on all aspects of life in various countries, including Indonesia. Various efforts have been made by both the central and regional governments in dealing with this problem, but in the process they are often faced with problems of differences in views and attitudes between levels of government, for example difference understanding that occurs between the Central Government and the Provincial Government of DKI Jakarta. This problem occurs because of weak inter-governmental coordination in making public policies. This ineffective inter-governmental relationship, of course, can cause public confusion in complying with all existing policies so that it will lead to not achieving the goal of handling cases. The purpose of this study is to analyze how inter-governmental relations in handling Covid-19 in Indonesia, especially between the Central Government and the Provincial Government of DKI Jakarta. The research method used in this research is literature study. While the data from the literature study is coded based on the indicators of the main theory. Result shows that there are a number of problems regarding the relation between central government and the government of DKI Jakarta Province in which most of the problems lie more on institutional and demographic factors rather than the other four factors.